Feasibility and safety of focal irreversible electroporation as salvage treatment for localized radio‐recurrent prostate cancer. (19th September 2017) - Scheltema, Matthijs J.; van den Bos, Willemien; Siriwardana, Amila R.; Kalsbeek, Anton M.F.; Thompson, James E.; Ting, Francis; Böhm, Maret; Haynes, Anne‐Maree; Shnier, Ron; Delprado, Warick; Stricker, Phillip D.
Abstract : Objectives: To evaluate the feasibility, safety, early quality‐of‐life (QoL) and oncological outcomes of salvage focal irreversible electroporation (IRE) for radio‐recurrent prostate cancer (PCa). Patients and Methods: Patients with localized, radio‐recurrent PCa without evidence of metastatic or nodal disease were offered focal IRE according to the consensus guidelines. Patients with a minimum follow‐up of 6 months were eligible for analysis. Adverse events were monitored using the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE version 4.0). Patient‐reported QoL data were collected at baseline, 6 weeks, 3, 6 and 12 months using the Expanded Prostate Cancer Index Composite (EPIC), the American Urological Association (AUA) symptom score and the 12‐item short‐from health survey (SF‐12) physical and mental component summary questionnaires. Oncological control was evaluated according to serial prostate‐specific antigen (PSA), 6‐month multiparametric magnetic resonance imaging (mpMRI) and 12‐month prostate biopsy. Wilcoxon's signed rank test was used to assess QoL differences over time in paired continuous variables. Results: A total of 18 patients were included in the analysis. The median follow‐up was 21 months. No high‐grade adverse events (CTCAE >2) or recto‐urethral fistulae occurred. No statistically significant declines were observed in QoL outcomes ( n = 11) on the EPIC bowel domain ( P = 0.29), AUA symptom score ( P = 0.77), or the SF‐12 physical ( P = 0.17) or SF‐12 mental component summary ( P = 0.77) questionnaires. At 6 months, patients who had undergone salvage therapy experienced a decline in EPIC sexual domain score (median of 38–24; P = 0.028) and urinary domain (median of 96–92; P = 0.074). Pad‐free continence and erections sufficient for intercourse were preserved in 8/11 patients and 2/6 patients at 6 months, respectively. The mpMRI was clear in 11/13 patients, with two single out‐field lesions (true‐positive and false‐positive, respectively). The median (interquartile range) nadir PSA was 0.39 (0.04–0.43) μg/L. Three and four patients experienced biochemical failure using the Phoenix and Stuttgart definitions of biochemical failure, respectively. Eight out of 10 of the patients were clear of any PCa on follow‐up biopsy, whereas two patients had significant PCa on follow‐up biopsy (International Society of Urological Pathology grade 5). Conclusion: Our short‐term safety, QoL and oncological control data show that focal IRE is a feasible salvage option for localized radio‐recurrent PCa. A prospective multicentre study (FIRE trial) has been initiated that will provide further insight into the ability of focal IRE to obtain oncological control of radio‐recurrent PCa with acceptable patient morbidity.